2014
DOI: 10.1049/mnl.2013.0600
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrodeposited crystallite size on interfacial adhesion strength of electroformed layers

Abstract: Microelectroforming is an important method for fabricating metal devices in microelectromechanical systems. However, the metal devices are limited by poor interfacial adhesion strength between the electroformed coating and the substrate. To improve the adhesion strength, the authors' research group presented a small current density deposition method. The purpose of this Letter is to investigate the mechanism of this method regarding the effect of the electrodeposited crystallite size. The mechanism is that a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Table 1 shows that the compressive stress is big when the crystallite size was small in the experiments. Meanwhile, the practical adhesion energy is reduced by the compressive stress in the electroforming layer [7]. Generally, the bigger the crystallite size, the lower the compressive stress and Figure 1 Relational graph of practical adhesion energy against crystallite size the greater the practical adhesion strength will be.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows that the compressive stress is big when the crystallite size was small in the experiments. Meanwhile, the practical adhesion energy is reduced by the compressive stress in the electroforming layer [7]. Generally, the bigger the crystallite size, the lower the compressive stress and Figure 1 Relational graph of practical adhesion energy against crystallite size the greater the practical adhesion strength will be.…”
Section: Resultsmentioning
confidence: 99%
“…These include the substrate surface, internal stress, hydrogen content in the film and the film thickness. Meanwhile, our previous work shows that the practical adhesion energy of the electroforming Ni layer on the Cu substrate is also influenced by the electroforming crystallite size [7]. Based on this, the equations between the electroforming crystallite size and the practical adhesion energy are investigated in this Letter.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The decrease in crystallite size of treated sample could be ascribed to biofield treatment that may cause increase in compressive stress that leads to increase in dislocation density and decrease in crystallite size. Zhao et al showed that increase in compressive stress in the material causes decrease in crystallite size [24]. Moreover, Schicker et al reported that crystallite size is inversely proportional to the milling speed, thus increase in milling speed decreases the crystallite size [25,26] improve its reaction rate [30] and it could be utilized for the synthesis of pharmaceutical compounds.…”
Section: Xrd Analysismentioning
confidence: 99%